MULTISCALE STRUCTURAL STUDY OF MIDDLE VAL D’ALA, NORTHERN SLOPE (PIEMONTE ZONE - WESTERN ALPS - ITALY) - Roda, Manuel; Assanelli, Matteo (Ofioliti, 2023)
This contribution presents a geological and structural study of the Val d’Ala metaophiolite complex (Lower Piemonte Zone) at the southern boundary of the Gran Paradiso Massif. Although this area was known since the 18th century for mining activity, a complete and modern multiscale structural study of the metaophiolite is still lacking. For this reason, we realized a structural map at 1:10.000 scale along the northern slope of middle Val d’Ala and we completed the study with a microstructural analysis. Here, serpentinites and metabasites are the dominant rocks and host hectometre-sized calcschist bodies, metre to decametre-sized metagabbro bodies, and some metre-sized eclogite lenses. All these lithologies belong to the Lower Piemonte Zone. In the upper part of the northern slope of the valley the tectonic contact with the gneisses of the Gran Paradiso Massif occurs. Four groups of superposed structures have been recognised by the multiscale investigation of the cross-cutting relationships between minerals, foliations, and folds. D1 relict fabrics occur in eclogites, metagabbros, and metabasites and are marked by omphacite, garnet, rutile, and glaucophane. Oldest metamorphic relicts in serpentinites are serpentine and rare amphibole, in calcschists are quartz and calcite, and in gneisses are quartz, garnet, and plagioclase. D2 structures consist of isoclinal folds and the S2 axial plane foliation that represents the dominant fabric and developed within all rock types. The S2 foliation is marked by glaucophane and epidote in the metabasites, metagabbros, and eclogites, serpentine and chlorite in the serpentinites, carbonate, quartz, white mica in the calcschists and quartz, plagioclase, and white mica in the gneisses. Locally green amphibole, chlorite and plagioclase replace clinopyroxene and glaucophane. The lithological boundaries and the tectonic contact between the Piemonte Zone metaophiolite and the gneisses of the Gran Paradiso Massif is parallel to S2. The D3 structures consists of a fold system with sub-horizontal axial plane (PA3) and axis (A3). The D4 fabric consists of isoclinal to open folds with sub-vertical dipping axial plane (PA4) and sub-horizontal axis (A4). D1 mineral assemblage suggests a metamorphic peak under eclogite-facies conditions for the metaophiolite complex, followed by re-equilibration under blueschist-facies conditions in which the contact with the gneisses of the Gran Paradiso Massif developed. The two units evolved together in lower pressure and temperature conditions.